Strengthening Justice Collaborator Protection Through LPSK-Managed Special Detention Facilities in Indonesia - Lia Gunawan; Dinalara Dermawati Butar Butar (Journal of Law, Society and Living Norms, 2026)
The feasibility of establishing special detention facilities for Justice Collaborators under the Witness and Victim Protection Agency (LPSK) was examined to address persistent failures in ensuring consistent physical and procedural security within existing detention centres. Separation of detention has long been recognized as a core component of protection, yet current institutional arrangements have left Justice Collaborators vulnerable to threats and operational inconsistencies. Using a doctrinal and conceptual legal approach supported by case-based assessment, the research identified clear normative gaps, institutional fragmentation, and practical constraints that undermine effective protection. The findings showed that LPSK holds structural advantages such as institutional independence, control over protection standards, and continuity of monitoring, while simultaneously lacking an explicit legal mandate and detailed operational framework to manage detention facilities. Results indicated that LPSK-managed detention centres are normatively justified but require a firm regulatory basis, standardized procedures, and coordinated mechanisms with law-enforcement agencies. The analysis concluded with recommendations for designing a legally grounded and operationally feasible model for such facilities.